2022
DOI: 10.1111/jfpp.16865
|View full text |Cite
|
Sign up to set email alerts
|

Plant protein enrichment effect on the physical, chemical, microbiological, and sensory characteristics of yogurt

Abstract: Yogurt is defined as a coagulated dairy product fermented by typical starter cultures (Adolfsson et al., 2004). Among various dairy products, yogurt is one of the most popular and highly accepted in the global market (Kumar et al., 2015). It is not surprising to see yogurt as one of the leader products among the other foods due to its functional properties in terms of nutrition and product design and alterations. Functional foods are foods that include active compounds that have clinically proven health benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…A different study reported that the addition of 0.5− 1.0% chickpea and pea proteins had no significant effect on the syneresis of bovine yogurt at day 1, but enhanced the WHC and reduced the syneresis during storage for 21 days Bulut, Adal, and Aktar. 8 In the present study, the increase in hydrophobic bonds due to the high amount of proteins in pea protein-added yogurt may have reduced the WHC and triggered higher syneresis. 33 3.2.…”
Section: Titratable Acidity Ph Value and Water-holdingmentioning
confidence: 54%
See 3 more Smart Citations
“…A different study reported that the addition of 0.5− 1.0% chickpea and pea proteins had no significant effect on the syneresis of bovine yogurt at day 1, but enhanced the WHC and reduced the syneresis during storage for 21 days Bulut, Adal, and Aktar. 8 In the present study, the increase in hydrophobic bonds due to the high amount of proteins in pea protein-added yogurt may have reduced the WHC and triggered higher syneresis. 33 3.2.…”
Section: Titratable Acidity Ph Value and Water-holdingmentioning
confidence: 54%
“…Previous studies have also reported similar findings, with the addition of chickpea and pea proteins at 0.5−1.0% having no significant effect on the pH of bovine yogurt Bulut, Adal, and Aktar. 8 Additionally, the addition of proteins from brewers' spent grains has been shown to enhance the growth of starter cultures and significantly reduce the pH of yogurt Naibaho et al 29 Furthermore, the addition of soybean proteins did not affect the pH of yogurt produced from either cow or camel milk. 30 However, the addition of hemp proteins at 5− 15% was found to significantly reduce the pH and increase the titratable acidity of yogurt produced with soymilk Xu et al 31 The reduction of pH values during fermentation is a result of the production of free amino acids from proteolysis and lactic acid from sugar catabolism during the growth of the starter cultures, L. bulgaricus and S. thermophilus, which grow synergistically.…”
Section: Titratable Acidity Ph Value and Water-holdingmentioning
confidence: 99%
See 2 more Smart Citations
“…The storage period additionally reduced the pH value from 4.63 on the first day to 4.22 on the 21st day of yoghurt storage and, respectively, from 4.41 to 3.91 in the yoghurt with a 3% additive. On the other hand, Bulut et al [ 32 ] showed that added plant protein increased titratable acidity values during storage. Abdel-Hamid et al [ 33 ] assessed the variability in the physicochemical parameters of yoghurts with the addition of Rubus suavissimus S. Lee Chinese sweet tea extract.…”
Section: Physicochemical Changes In Yoghurtsmentioning
confidence: 99%